Still About Oil? - Shimshon Bichler; Jonathan Nitzan (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2014)
During the late 1980s and early 1990s, we identified a new Middle East phenomenon that we called 'energy conflicts' and argued that these conflicts were intimately linked with the global processes of capital accumulation. This paper outlines the theoretical framework we have developed over the years and brings our empirical research up to date. It shows that the key stylized patterns we discovered more than twenty years ago – along with other regularities we have uncovered since then – remain pretty much unchanged: (1) conflict in the region continues to correlate tightly with the differential profits of the Weapondollar-Petrodollar Coalition, particularly the oil companies; (2) dominant capital continues to depend on stagflation to substitute for declining corporate amalgamation; and (3) capitalists the world over now need inflation to offset the spectre of debt deflation. The convergence of these interests bodes ill for the Middle East and beyond: all of these groups stand to benefit from higher oil prices, and oil prices rarely if ever rise without there being an energy conflict in the Middle East.
Keywords: 330; crisis; differential accumulation; energy conflicts; Middle East; Petro-Core